Performance of Polyurethane Adhesive in Hardwood Cross-Laminated Timber - Bradia T. Henfield; Tamara Suely Filgueira Amorim Franca; Frederico Franca; Franklin Quin Jr; Rachel A. Arango; Katie M. Ohno (BioResources)
As hardwood cross-laminated timber (CLT) gains attention due to its construction potential, understanding the interaction between hardwood panels and adhesives is critical for ensuring structural integrity and longevity of buildings. This study investigated adhesive bonding properties in hardwood CLT made from red oak (Quercus spp. L.), sweet gum (Liquidambar styraciflua L.), and yellow poplar (Liriodendron tulipifera L.), using southern pine (Pinus spp. L.) (SP) as a control. Adhesive performance was evaluated through shear block tests to assess the bond line shear strength and delamination tests to measure the bond durability under cyclic moisture conditions. Results indicated significant variations in adhesive performance among the hardwood CLT specimens compared to SP, with differences in both shear strength and delamination resistance. Red oak CLT exhibited significantly greater delamination compared to all the other species. The delamination observed among the yellow poplar samples was not significantly different than that of the control SP samples. The shear block results indicated that the bond line strength of both red oak and yellow poplar samples was significantly greater than that of the control samples. These findings provide critical insights into selecting and optimizing adhesives for hardwood CLT production.